Roadmap for action on Risk Assessment of Combined Exposure to Multiple Chemicals (RACEMiC). Issue 10 (13th October 2022) - de Jong, Esther; van der Voet, Hilko; Marx‐Stoelting, Philip; Bennekou, Susanne Hougaard; Sprong, Corinne; Bloch, Denise; Burchardt, Alina; Lasch, Alexandra; Opialla, Tobias; Rotter, Stefanie; Wedebye, Eva Bay; Zwartsen, Anne; et al.
Abstract: EFSA's aim by 2030, is that the Agency and its partners will be equipped for the routine implementation of human health risk assessment to multiple chemicals, across EFSA's domains of activity. To facilitate this effort, a roadmap for action has been developed by mapping the methods, data and tools that are currently available for mixture risk assessment and identifying current scientific gaps including challenges and blockers. The results shows that extensive methods, data and tools are available for dietary mixture risk assessment for pesticides, but that several scientific gaps still exist for the non‐dietary mixture exposure to pesticides. For food additives and for certain contaminants, the regulatory readiness for mixture risk assessment was also found to be fairly high compared to food contact materials and cross‐silo mixture risk assessment. The scientific gaps identified were prioritised according to their impact on the implementation of mixture risk assessment and, as a result, ten multi‐annual project proposals were defined to address these scientific gaps on the short‐term, mid‐term and long‐term. The roadmap also proposes and prioritises a number of working areas in the regulatory domains of pesticides, food contact materials, contaminants, food additives, as well as in the overarching domain of chemicals. Besides the scientific proposals, recommendations to improve stakeholder engagement and communication on mixture risk assessment was investigated. These included, among others, creating an online catalogue of tools, methods and data for mixture risk assessment, as well as the organisation of regular webinars/workshop to promote exchange of information between stakeholders and making more efficient use of national communication hubs for food safety in communicating with the general public.